First-contact incidence of psychosis in north-eastern Italy: influence of age, gender, immigration and socioeconomic deprivation. (2nd January 2018) - Lasalvia, Antonio; Bonetto, Chiara; Tosato, Sarah; Zanatta, Gioia; Cristofalo, Doriana; Salazzari, Damiano; Lazzarotto, Lorenza; Bertani, Mariaelena; Bissoli, Sarah; De Santi, Katia; Cremonese, Carla; De Rossi, Moreno; et al.
Abstract : Background: Considerable variations in the incidence of psychosis have been observed across countries, in terms of age, gender, immigration status, urbanicity and socioeconomic deprivation. Aims: To evaluate the incidence rate of first-episode psychosis in a large area of north-eastern Italy and the distribution of the above-mentioned risk factors in individuals with psychoses. Method: Epidemiologically based survey. Over a 3-year period individuals with psychosis on first contact with services were identified and diagnosed according to ICD-10 criteria. Results: In total, 558 individuals with first-episode psychosis were identified during 3 077 555 person-years at risk. The annual incidence rate per 100 000 was 18.1 for all psychoses, 14.3 for non-affective psychoses and 3.8 for affective psychoses. The rate for all psychoses was higher in young people aged 20–29 (incidence rate ratio (IRR) = 4.18, 95% CI 2.77–6.30), immigrants (IRR = 2.26, 95% CI 1.85–2.75) and those living in the most deprived areas (IRR = 2.09, 95% CI 1.54–2.85). Conclusions: The incidence rate in our study area was lower than that found in other European and North American studies and provides new insights into the factors that may increase and/or decrease risk for developing psychosis.